Best Practice Guideline - DEGUM Recommendations on Breast Ultrasound - Part I - Examination technique, DEGUM ultrasound criteria, and documentation - Bader, Werner; Vogel-Minea, Claudia Maria; Blohmer, Jens-Uwe; Duda, Volker; Eichler, Christian; Fallenberg, Eva; Farrokh, Andre; Golatta, Michael; Gruber, Ines; Hackeloeer, Bernhard-Joachim; Heil, Joerg; Madjar, Helmut; et al. (Ultraschall in der Medizin, 2021)
For many years, breast ultrasound has been used in addition to mammography as an important method for clarifying breast findings. However, differences in the interpretation of findings continue to be problematic 1 2 . These differences decrease the diagnostic accuracy of ultrasound after detection of a finding and complicate interdisciplinary communication and the comparison of scientific studies 3 . In 1999, the American College of Radiology (ACR) created a working group (International Expert Working Group) that developed a classification system for ultrasound examinations based on the established BI-RADS classification of mammographic findings under consideration of literature data 4 . Due to differences in content, the German Society for Ultrasound in Medicine (DEGUM) published its own BI-RADS-analogue criteria catalog in 2006 3 . In addition to the persistence of differences in content, there is also an issue with formal licensing with the current 5th edition of the ACR BI-RADS catalog, even though the content is recognized by the DEGUM as another system for describing and documenting findings. The goal of the Best Practice Guideline of the Breast Ultrasound Working Group of the DEGUM is to provide colleagues specialized in senology with a current catalog of ultrasound criteria and assessment categories as well as best practice recommendations for the various ultrasound modalities.
CRIS-Team WoS Importer:2022-02-25